(untitled) (Центральноазиатский журнал образования и инноваций, 2025)
This article explores the modern methodological principles and practical techniques used in teaching visual arts in primary school. It examines how structured teaching strategies, age-appropriate content, and integration of technology can foster creativity and artistic skills in children. The IMRAD (Introduction, Methods, Results, and Discussion) framework is used to analyze the pedagogical effectiveness of visual arts instruction. Results show that a learner-centered, interactive approach improves artistic competencies and motivation among young learners.